Iron impurity in zircon by DFT computations - Stashans, A. (2013)
A single Fe impurity impact on the properties of ZrSiO4 low pressure phase (zircon) has been addressed in the present work. First-principles density functional theory and generalized gradient approximation have been exploited throughout the study. Strong electron correlation effects not included in the density-functional formalism are treated by a Hubbard-type on-site Coulomb repulsion approach. Our results provide evidence over occurrence of a local magnetic moment in the material. Reduction in the band-gap width, changes in chemical bonding and microstructure of the defective region have been discussed as well. © 2013 World Scientific Publishing Company.